Analisis Kebutuhan Media Pembelajaran Bagan dan Audio pada Materi Wudhu Kelas VII MTs Muslimat NU Palangkaraya - Normila, Cahya; Safitri, Novia (Lembaga Yasin AlSys, 2024)
This research is based on the need for creative and interesting Chart and Audio Learning Media, which is still minimally used by teachers in Fiqh learning. Learning media that combines charts and audio can be the right solution to help improve students' understanding of ablution material at MTs Muslimat NU Palangka Raya. The aim of this research is to analyze students' needs by creating learning media that does not depend on advanced technology, but is still effective, which can be implemented in the Fiqh learning process at MTs Muslimat NU Palangka Raya. This research uses a qualitative descriptive method. Data collected through observation and distributing questionnaires to class VII students at MTs Muslimat NU. From the distribution of questionnaires, results were obtained which showed that students really need Chart and Audio media in the learning process. In conclusion, this media is needed by students as an alternative learning media to replace the limitations of technology in learning at school, one of which is in learning Fiqh, Wudhu material for class VII.